Characterization Alloys of the Sn-Zn System Produced by Melt Spinning - Russi,Luis Gustavo Cordiolli (2019)
The objective of this work was the conformation of ribbons from Sn3Zn alloy and Sn pure, using the melt-spinning fast cooling technique, in order to investigate the applicability as biomaterial. The ribbons were coated with 1% poly-caprolactone (PCL) and subsequent incorporation of silver nanoparticles (NPAg). In the uncoated ribbon was observing a surface roughness due of agglomerate caused by rapid solidification. In the ribbon coated with PCL and NPAg incorporation, it was observed that these compounds adhered to the ribbon. X-ray diffraction analysis showed no ribbons amorphization. The analysis by differential scanning calorimetry, indicated that the Sn3Zn ribbon had a lower melting temperature (198.1°C) than the Sn ribbon (228.7°C). The microhardness of Sn3Zn ribbon was 13.38 HV and Sn ribbon was 11.00 HV, both for the face without contact with the cooling wheel. In the bioactivity assays, performed in simulated body fluid medium, all samples showed apatites formation after four weeks of testing.